KEPASTIAN HUKUM PENANAMAN MODAL ASING DALAM BENTUK PERSEROAN TERBATAS (NAAMLOZE VENNOTSCHAP) - Eva Jayanti, Komang; Mas Ariani, Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper entitled Law Certainty Of Foreign Invesment In The Form Of CompanyLimited By Shares (Naamloze Vennotschap). This paper uses normative analyticalmethods and the statute approach. Foreign invesment has important role to advance thenational economy. Trough this writing, the legal certainty of foreign investment in theform of company limited by shares shall be elucidated.
Keywords: law certainty, foreign invesment, company limited by shares